Dietary phytochemical index is associated with systemic inflammation, insulin resistance, and gut microbiota-derived metabolites in individuals with obesity: A cross-sectional study - Lingtao Zheng; Yanjiao Shen (PLoS ONE, 2026)
Background Obesity is linked to chronic inflammation, insulin resistance, and gut microbiota dysbiosis, partly via TMAO. This study investigates associations between dietary patterns, as indexed by the Dietary Phytochemical Index (DPI), with insulin resistance, inflammatory markers, and TMAO. Methods In this cross-sectional study, 600 adults with obesity (BMI ≥ 30 kg/m²) without diagnosed comorbidities were evaluated. Dietary intake was assessed using a validated 110-item FFQ, and the DPI was computed. Fasting blood samples were analyzed for glucose, insulin, HOMA-IR, lipid profile, CRP, IL-6, TNF-α, LBP, adiponectin, and TMAO. Multivariable regression and mediation analyses were performed. Results Participants in the highest DPI quartile exhibited lower mean BMI, waist circumference, and fat mass compared to those in the lowest quartile. They also had lower fasting plasma glucose (4.52 ± 0.06 mmol/L vs. 5.92 ± 0.24 mmol/L; P < 0.001), lower insulin concentrations (65.6 ± 2.4 pmol/L vs. 120.4 ± 18.0 pmol/L; P < 0.001), and lower HOMA-IR values (1.90 ± 0.09 vs. 4.59 ± 0.82; P < 0.001). Higher DPI was associated with lower concentrations of CRP, TNF-α, and TMAO, and higher concentrations of adiponectin and HDL-C (all P < 0.001). Conclusions Higher DPI was associated with lower systemic inflammation and better insulin sensitivity. These findings highlight the potential role of phytochemical-rich diets in supporting insulin resistance and metabolic disturbances among obese adults; however, prospective randomized controlled trials are required to confirm these associations and establish causality.